Methodological instructions for performing calculation tasks in robotics for the courses "Robot Mechanics", "Software and Hardware Technologies for Creating Robotic Systems" and "Methods of Controlling the Motion of Robotic Systems" - Andreyev, Y. M.; Shabanov, H. V. (National Technical University "Kharkiv Polytechnic Institute", 2025)
Methodological Guidelines contain tasks (17 variants) for students to solve com-putational problems as part of independent work within the robotics mechanics course. Each variant involves creating analytical models of a planar manipulator using the spe-cialized computer algebra system KiDyM (CASC KiDyM) based on the schematic pro-vided in the task variant and performing the relevant kinematic and dynamic calculations for the respective mechanism. Each task includes up to five calculations of forward and inverse kinematics, forward and inverse dynamics and the determination of the manipu-lator's workspace. The results of the calculations are graphical and animated data that demonstrate the kinematic and dynamic behavior of the robotic device. To assist students, all stages of computer modeling and calculations are explained in detail. The KiDyM program, developed by the Department of Computer Modeling of Processes and Systems, is used for calculations. Following the provided instructions, students install the program on their computers. The program enables syntactic and se-mantic data validation, helping students identify errors and perform calculations in an interactive mode. The Methodological Guidelines are intended for full-time and distance learning students for use in practical and laboratory sessions, as well as for independent student work.
Keywords: methodical instructions; information technology; software; robotics; manipulators; kinematics; computer systems